Blind Adenoidectomy versus Blend Adenoidectomy: A Comparative Analysis - Dr. Shuklima Sengupta; Dr. Kripamoy Nath (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Adenoids are masses of lymphoid tissues, situated at nasopharynx. Children with enlarged adenoids exhibit chronic nasal blockage, rhinorrhea, mouth breathing, snoring, etc., followed by hearing problems and delayed speech, thus requiring adenoidectomy. Due to the enormous quantity of adenoidectomies performed, surgeons must effectively consider safety, accuracy, and results while selecting from the several surgical adenoidectomy techniques available, such as curettage, microdebrider, bipolar coagulation, stripping under endoscopic control, and coblation. The Aim of this study is to compare safety and efficacy between conventional curettage adenoidectomy verses comprehensive Microdebrider with Coblation adenoidectomy. This is a Retrospective Observational Study of 1year, including 80 patients aged 3-15 years, with symptoms of upper airway obstruction undergoing adenoidectomy. Children with syndromes, bleeding disorders, cranio-facial abnormalities were excluded. The sample was divided into two groups, Group A: 40 patients who underwent Conventional Curettage adenoidectomy and Group B: 40 patients who underwent Microdebrider with Coblation adenoidectomy. The operating time, amount of bleeding, post-operative pain, days to resume regular diet and activity, residual tissues were compared and analysed. The operating time was approximately 10mins higher, Intraoperative bleeding 15ml lesser with lesser post operative pain found in Group B. Patients resumed regular meal and activity 0.5-2 days earlier in Group B. The recurrence of symptoms with residual adenoid tissues was 32.5% more in Group A. Through this study it is found that, Blend adenoidectomy is superior to Blind adenoidectomy with respect to lesser intraoperative haemorrhage, post-operative pain and recurrence, early return to normal diet and activities but with increased operating time.